Atrial Fibrillation in Hypertrophic Cardiomyopathy: Is the Extent of Septal Hypertrophy Important? - Kyoung-Min Park (PLoS ONE, 2016)
Hypertrophic cardiomyopathy (HCM) is a cardiac disease associated with a high incidence of atrial fibrillation (AF). Recent studies have suggested that interventricular septum thickness may influence the risk stratification of patients with AF. We evaluated the effects of septal hypertrophy on morbidity and mortality in patients with HCM. Patients were followed for a median of 6.1 years and were divided into two groups according to the extent of septal hypertrophy. A total of 1,360 HCM patients were enrolled: 482 (33%) apical or apicoseptal, 415 (28%) asymmetric septal, 388 (27%) basal septal, 38 (2.6%) concentric, and 37 (2.5%) diffuse and mixed type. Ninety-two all-cause deaths and 21 cardiac deaths occurred. The total event rates were significantly higher for patients with HCM with more extensive septal hypertrophy (group A) compared to those with HCM ± focal septal hypertrophy (group B), regardless of type (p<0.001). Arrhythmias occurred in 502 patients, with a significantly higher incidence in group A than in group B (p<0.001). Among patients with arrhythmias, the incidence of AF was significantly higher in group A than group B (p<0.001). In univariate Cox analysis, a greater extent of septal hypertrophy (p<0.001), E/E´ ratio (p = 0.011), and mitral regurgitation grade (p = 0.003) were significantly associated with developing AF. In multivariate Cox analyses, a greater extent of septal hypertrophy [odds ratio (OR) 5.44 (2.29-12.92), p<0.001] in patients with HCM was significantly associated with developing AF. In conclusion, a greater extent of septal hypertrophy is an independent predictor of progression to AF in patients with HCM.